Clinical subsets associated with different anti-aminoacyl transfer RNA synthetase antibodies and their association with coexisting anti-Ro52. Issue 3 (3rd May 2016) - Yamasaki, Yoshioki; Satoh, Minoru; Mizushima, Machiko; Okazaki, Takahiro; Nagafuchi, Hiroko; Ooka, Seido; Shibata, Tomohiko; Nakano, Hiromasa; Ogawa, Hitoshi; Azuma, Kohei; Maeda, Akihiko; Tonooka, Kumiko; et al.
Abstract: Objective : To characterize clinical features of polymyositis/dermatomyositis (PM/DM) patients with different anti-aminoacyl transfer RNA synthetase (ARS) antibodies and their association with anti-Ro52. Methods : Autoantibodies in sera from 97 Japanese patients (36 PM, 56 DM, and 5 clinically amyopathic DM), who satisfied Bohan and Peter or modified Sontheimer's criteria, were characterized by immunoprecipitation and enzyme-linked immunosorbent assay. Clinical information was from medical records. Features associated with different anti-ARS and anti-Ro52 antibodies were analyzed. Results : The prevalence of anti-ARS was similar to other studies (Jo-1, 22%; EJ, 4%; OJ, 1%; PL-12, 1%), except for a high prevalence of anti-PL-7 (12%), which allowed us to characterize patients carrying this specificity. Serum creatine kinase >3000 IU/l was less common in anti-PL-7-positive patients (57%) than anti-Jo-1-positive patients (18%) ( p  = 0.0328) and was not found in anti-EJ-positive individuals. Interstitial lung disease was common in anti-ARS-positive patients (97%) ( p  < 0.0001 vs. 48% in anti-ARS-negative). Anti-Ro52 antibodies were frequently detected with anti-ARS (59%) (57% in anti-Jo-1, 67% in anti-PL-7) (vs. 21% in anti-ARS-negative, p  < 0.0002). Anti-Ro52 was associated with overlap syndrome (26%) (vs. 7% in anti-Ro52-negative, p  = 0.0119). Conclusions : Patients with different anti-ARS in combination with anti-Ro52 appear to be associated with distinctive clinical subsets.